European trade policy in interesting times. Issue 7 (10th November 2017) - Young, Alasdair R.
Abstract: This article draws out the implications of the other contributions to this special issue and reflects on their implications for the development of the European Union's trade policy. It makes three main arguments. First, intense popular opposition to (some) trade agreements has disrupted the EU's efforts to manage the tensions among the objectives of policy-making efficiency, policy effectiveness and political legitimacy. Second, public opposition to trade agreements is profoundly shaped by how the threat from trade has been framed. Third, the politics of different free trade agreements are even more interconnected than has been previously acknowledged. Taken together these arguments mean that EU trade policy is being made in particularly 'interesting times' and is, therefore, especially challenging.